LANGUAGE LEARNING STRATEGIES AND SELF-REGULATION (Web of Teachers: Inderscience Research, 2025)
Self-regulation in language learning refers to the ability of learners to plan, monitor, and evaluate their own learning processes. This approach encourages learners to take control of their educational journey, making them active participants in their language acquisition. Language teaching that incorporates self-regulation strategies helps students set clear goals, reflect on their learning, and adapt strategies based on progress. Teachers play a crucial role in fostering self-regulation by creating supportive environments, providing constructive feedback, and modeling effective learning strategies. While self-regulated learning offers numerous benefits, such as improved proficiency, motivation, and lifelong learning habits, it also presents challenges, including lack of confidence, procrastination, and overwhelming content. This article explores the relationship between language teaching and self-regulation, highlighting effective strategies for both teachers and learners, and emphasizes the importance of promoting self-regulated learning for enhanced language acquisition and long-term success.